Impact of cancer in patients with peripheral artery disease - Souza Lima, Verônica de Fátima (2022)
Introduction and Objective: The impact of cancer in patients with PAD on the level of daily physical activity, functional capacity, cardiovascular function and quality of life is not yet known, thus being the objective of this present study. Methods: Cross-sectional study with 299 patients. Physical activity level (accelerometer), functional capacity (6-minute walk test, Handgrip, Short Physical Performance Battery, Walking Impairment Questionnaire-WIQ and the Walking Estimated-Limitation Calculated by History), cardiovascular function (brachial blood pressure, variability of heart rate and arterial stiffness) and quality of life (WHOQOL-bref) were compared between patients with PAD with and without a history of cancer.Results: Patients with PAD and cancer (N=27) performed better in the distance and speed domains of the WIQ (21±37 vs 14±26, p=0.036; 29±18 vs 22±15, p=0.022, respectively) compared to PD patients without cancer. The other parameters were similar between groups. Conclusion: Patients with PAD and cancer had better results for subjectively assessed functional capacity.